Assessing horizontal force production in resisted sprinting: Computation and practical interpretation - Cross, M. R.; Tinwala, F.; Lenetsky, S.; Brown, S. R.; Brughelli, M.; Morin, J.-B.; Samozino, P. (International Journal of Sports Physiology and Performance, 2019)
The assessment of horizontal force during overground sprinting is increasingly prevalent in practice and research, stemming from advances in technology and access to simplified yet valid field methods. As researchers search out optimal means of targeting the development of horizontal force, there is considerable interest in the effectiveness of external resistance. Increasing attention in research provides more information surrounding the biomechanics of sprinting in general and insight into the potential methods of developing determinant capacities. However, there is a general lack of consensus on the assessment and computation of horizontal force under resistance, which has resulted in a confusing narrative surrounding the practical applicability of loading parameters for performance enhancement. As such, the aim of this commentary was twofold: to provide a clear narrative of the assessment and computation of horizontal force in resisted sprinting and to clarify and discuss the impact of methodological approaches to subsequent training implementation. Horizontal force computation during resisted sleds, a common sprint-training apparatus in the field, is used as a test case to illustrate the risks associated with substandard methodological practices and improperly accounting for the effects of friction. A practical and operational synthesis is provided to help guide researchers and practitioners in selecting appropriate resistance methods. Finally, an outline of future challenges is presented to aid the development of these approaches.